FORMING A DIGITAL PEDAGOGICAL ENVIRONMENT THROUGH MOBILE APPLICATIONS IN PHYSICAL EDUCATION (ON THE EXAMPLE OF THE PJT MOBILE APPLICATION) (Universal International Scientific Journal, 2026)
This article analyzes the theoretical and practical aspects of creating a digital pedagogical environment based on mobile technologies in physical education. It is emphasized that the rapid development of information and communication technologies requires new pedagogical approaches in the educational process. On this basis, mobile applications are considered as an important innovative tool in teaching physical education. The study highlights the possibilities of organizing the educational process within the framework of the mobile learning concept and the methodological foundations of its optimization. The pedagogical capabilities of the PJT (Professional Physical Education) mobile application created by the author are also analyzed. The results show that mobile technologies are effective in increasing educational efficiency, increasing student motivation, and monitoring physical development.
Keywords: physical education, mobile learning, digital pedagogical environment, mobile applications, sports education, innovative pedagogy, PJT mobile application.